Advanced oil recovery associated with carbon capture and storage (Research, Society and Development, 2022)
Advanced Oil Recovery (EOR) techniques have enormous potential in the oil and gas industry. Among the possibilities to increase the useful life of the reservoirs is EOR acting in conjunction with the use of carbon dioxide (CO2) captured from anthropogenic and natural sources. Given the high costs associated with new oil explorations, there is a growing interest in the search for the recovery of the remaining oil, via advanced or tertiary recovery techniques, such as EOR, exploring the availability of oil contained in the reservoirs. The growing concern with the use of non-renewable and promising resources of greenhouse gases (GHG), such as CO2, especially for energy generation, has triggered the search for technologies to mitigate GHG emissions. Among these technologies, the Carbon Capture and Storage (CCS) stands out, which captures CO2 from anthropogenic sources, and it is later used as an input in industry or stored in geological formations. CSS, in conjunction with EOR, directs the use of CO2 to increase oil production concurrently with its storage. This work, through a literature review, brought data that demonstrate how the use of CO2 has been widely used for EOR in onshore oil exploration, and facing challenges for the expansion of its use in offshore fields. It was identified that natural sources of CO2 are predominant, that is, there is no significant contribution to reducing GHG emissions.